The Impact of Maritime Transport Development on Logistics Operators in the Cross-Docking Process - Gawron, Tobiasz (Towards Sustainable Transport in Logistics and International Trade, 2025)
The aim of this chapter was to examine the impact of the COVID-19 pandemic on logistics operators and to evaluate the effectiveness of implementing procedures and mapping logistics processes. The study was based on an analysis of responses from logistics company representatives, who assessed the pandemic’s effects on maritime transport, supply disruptions, and organizational challenges. The results indicate that the pandemic negatively affected the operations of logistics firms; however, the proper implementation of logistics procedures contributed positively to optimizing activities and improving operational efficiency. The findings highlight the crucial role of maritime transport development and logistics infrastructure, particularly in the context of cross-docking, and emphasize the need to introduce modern solutions and improvements in logistics processes that can help companies respond more effectively to crises and changing market conditions.